The Role of Nuclear Energy in Uzbekistan (Texas Journal of Engineering and Technology, 2022)
This article describes the ongoing reforms in the field of nuclear energy in Uzbekistan. In addition, the problems and prospects of nuclear energy, the main problems that may arise in the field are highlighted.